2010
DOI: 10.1111/j.1937-5956.2009.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

ABC Classification: Service Levels and Inventory Costs

Abstract: ABC inventory classifications are widely used in practice, with demand value and demand volume as the most common ranking criteria. The standard approach in ABC applications is to set the same service level for all stock keeping units (SKUs) in a class. In this paper, we show (for three large real life datasets) that the application of both demand value and demand volume as ABC ranking criteria, with fixed service levels per class, leads to solutions that are far from cost optimal. An alternative criterion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
93
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 24 publications
(36 reference statements)
2
93
0
3
Order By: Relevance
“…Single-Criterion Inventory Classification (SCIC) methods are often used in practice with traditional criteria such as the demand value or the demand volume (Syntetos et al, 2009). These methods have also been analyzed for many decades by inventory researchers (Teunter et al, 2010). Furthermore more recently, Multi-Criteria Inventory Classification methods (MCIC) have been developed where a combination of criteria such as the lead time, the criticality, the price, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-Criterion Inventory Classification (SCIC) methods are often used in practice with traditional criteria such as the demand value or the demand volume (Syntetos et al, 2009). These methods have also been analyzed for many decades by inventory researchers (Teunter et al, 2010). Furthermore more recently, Multi-Criteria Inventory Classification methods (MCIC) have been developed where a combination of criteria such as the lead time, the criticality, the price, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two research works have recently tackled this issue by proposing new classification methods that aim to improve the inventory performance whilst classifying the SKUs. (Teunter et al, 2010) have proposed a new ABC classification method based on a cost criterion for ranking the SKUs. The classification criterion is based on the demand rate, the inventory holding cost and the order quantity of each SKU.…”
Section: Introductionmentioning
confidence: 99%
“…The ABC method is widely used to streamline an organization, and it is commonly used to manage inventory with a large number of distinct items 24 and may be suitable to classify production line operations and thereby increase effectiveness 25 of production parameters' optimization.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the fact that the classical ABC-method is easy to understand and implement, it is only successful when the classification considers one single criterion. Teunter et al [23] have shown that the ABC ranking criteria as cost value and demand volume can lead to inefficient solutions. This has led researchers and practitioners to extend the traditional ABCclassification to a multi-criteria ABC-analysis including other parameters like unit cost, fail rate and lead time.…”
Section: Introductionmentioning
confidence: 99%